2015
DOI: 10.1007/s00408-015-9685-y
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Administration for Chronic Respiratory Failure: A Randomized Dose-Comparison Trial

Abstract: Improvements in the oxygen uptake capacity were greater in patients receiving 2 μg/kg ghrelin twice daily for 3 weeks than in those receiving 1 μg/kg, although exercise tolerance was similar between groups at the end of the 3-week treatment period. Thus, a twice daily dose of 2 μg/kg ghrelin is recommended over 1 μg/kg ghrelin for patients with chronic respiratory failure and weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…In contrast with our previous study and the present main multicenter dose‐finding study , 3‐week high‐dose ghrelin‐PR treatment did not significantly improve the primary outcome of mean change in peak truenormalV˙o 2 compared with low‐dose ghrelin in the present population; there are two possible explanations. (i) The mean change from pretreatment to 3 weeks of high‐dose ghrelin‐PR treatment in the present study had a larger SD compared with that of the previous study , which means that (a) there were both “responders” and “nonresponders” to high‐dose ghrelin with PR, so that investigating which patients are likely to benefit from ghrelin treatment with PR is likely to become an issue to be addressed in the future; and (b) the small number of enrolled patients might have affected the results.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with our previous study and the present main multicenter dose‐finding study , 3‐week high‐dose ghrelin‐PR treatment did not significantly improve the primary outcome of mean change in peak truenormalV˙o 2 compared with low‐dose ghrelin in the present population; there are two possible explanations. (i) The mean change from pretreatment to 3 weeks of high‐dose ghrelin‐PR treatment in the present study had a larger SD compared with that of the previous study , which means that (a) there were both “responders” and “nonresponders” to high‐dose ghrelin with PR, so that investigating which patients are likely to benefit from ghrelin treatment with PR is likely to become an issue to be addressed in the future; and (b) the small number of enrolled patients might have affected the results.…”
Section: Discussioncontrasting
confidence: 99%
“…After each patient was registered, synthetic human ghrelin 120 μg or 60 μg was dissolved in 2 mL of 3.75% mannitol solution in a vial. All vials prepared were stored frozen at −30°C from the time of dispensing until the time of preparation for injection as previously described .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kodama and colleagues showed ghrelin to suppress airway inflammation and increase functional exertion capacity in patients with chronic respiratory failure [73]. Miki and colleagues later showed that ghrelin enhanced exercise capacity, expiratory pressure and improved respiratory symptoms in COPD patients [83,243] and showed benefits on exertional dyspnea [244], These effects may be dose-dependent [245,246]. For lung cancer, treatment with the potent ghrelin analog anamorelin has shown benefits on appetite, lean mass retention, performance and quality of life [133,134,135].…”
Section: Pulmonary Diseasementioning
confidence: 99%
“…There are wide difference among studies in the definition of cachexia, although some of them have taken weight loss into account as part of the definition. [27][28][29][30][31][32][33] Four interventional studies using ghrelin and octanoic acid-rich formula have been reported in the field of COPD, including two studies with weight loss >7.5% over 6 months 32,33 and 2 studies with BMI <21 kg/m 234, 35 as the definition of cachexia. On the other hand, there is no published interventional research targeting cachexia in cancer, heart failure, and CKD.…”
Section: Recent Cachexia Research In Japanmentioning
confidence: 99%